Pengaruh Pendekatan Pembelajaran Realistic Mathematics Education dan Contextual Teaching Learning terhadap Pemahaman Konsep dan Komunikasi Matematis - Lubis, Mara Samin (IAIN PADANGSIDIMPUAN, 2019)
This research was conducted to see the extent of students' understanding of concepts and mathematical communication after being treated with learning using the RME and CTL approaches. The approach used in this research is quantitative with a type of quasi-experimental research. The population as well as the sample in this study were 2 classes with a total of 70 XI MAS PAB 2 Medan Estate students. Next to find out the understanding of concepts and mathematical communication students are given a description test. To process the data obtained using ANACOVA; The results of the data analysis test concluded: the level of understanding of the concepts of students who were treated with the RME approach was lower in influence than students who were treated with the CTL approach. The mathematical communication of students who were treated with the RME approach was less influential than students who were treated with the CTL approach. The level of understanding of mathematical concepts and communication of students who were treated with the RME learning approach was lower in influence than students who were treated with the CTL learning approach. Data analysis concluded that there was an interaction effect of applying the learning approach to students' understanding of concepts and mathematical communication.